Insights from fifteen years of real-world development, testing and implementation of youth digital mental health interventions - Shane Cross; Shaminka Mangelsdorf; Lee Valentine; Shaunagh O'Sullivan; Carla McEnery; Isabelle Scott; Tamsyn Gilbertson; Shona Louis; Jon Myer; Ping Liu; Niel Mac Dhonnagáin; Tom Wren; et al. (Internet Interventions, 2025)
This paper reviews the current evidence and synthesizes fifteen years of real-world development, testing, and implementation of digital mental health interventions (DMHIs) for young people. Drawing on the work of Orygen Digital, we outline the evolution of interventions including the Moderated Online Social Therapy (MOST) platform, the Mello app, and a suite of virtual reality-based therapies; all developed to meet the complex clinical, developmental, and service needs of youth aged 12 to 25.We identify ten key challenges and opportunities encountered in designing, developing and implementing these DMHIs: (1) meaningful co-design; (2) sustained user engagement; (3) personalization and transdiagnostic targeting; (4) optimizing intensities of human support; (5) leveraging peer support and social networking; (6) embedding DMHIs in clinical services; (7) blending digital and face-to-face care; (8) building data infrastructure and learning health systems; (9) developing sustainable and scalable business models; and (10) preparing DMHIs for large language models. Each theme reflects both achievements and persistent challenges, and is illustrated through a synthesis of the current evidence and real-world insights from our clinical trials and national-scale service implementations.Our approach is grounded in various frameworks including clinical staging, self-determination theory, supportive accountability, and minimally disruptive medicine. Emerging innovations such as just-in-time adaptive interventions, extended reality (XR) therapies, stratified treatment models, and large language models offer promising future pathways for greater personalization, engagement, effectiveness, and scalability.Our findings highlight the potential value of context-sensitive, co-designed, and system-integrated DMHIs, while also emphasising enduring limitations such as variable engagement, implementation barriers, and population-specific adaptation. Moving beyond controlled efficacy trials toward agile, real-world learning health systems will be essential to realising the full potential of DMHIs in transforming youth mental health care.